Pengembangan Permainan Ular Tangga Bernuansa Islami Untuk Pembelajaran IPA - Yuni, Yesi Andra; Zulhanan, Zulhanan; Sodikin, Sodikin (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to; 1) identifies the eligibility ladder snake game in Islamic learning IPA; 2) know the response of the students against Islamic ladder snake game in learning the IPA as a learning resource that will be developed. Methods in this study using the method of research and development (Research and Development) model Borg and Gall that have been developed through dimodifiksi; 1) potential and problems; 2) data collection; 3) product design; 4) validation of the design; 5) revision of the product; 6) free trial products; 7) revision of the product. Taken only up to seven steps because of the limitations. The research data was collected by using the sheet validation, the now and the response of the learners. The results of this research are; 1) game development ladder snake islami in IPA is well worth learning is used in learning based on the results of validation experts, namely 93.5% material experts, 80.5%, media expert and expert religion 100%; 2) on the response of the students performed at the three schools earn a percentage of the feasibility of an average of 93% with a very worthy category.Abstrak: Penelitianini bertujuan untuk; 1) mengidentifikasi kelayakan permainan ular tangga islami dalam pembelajaran IPA; 2) mengetahui respon peserta didik terhadap permainan ular tangga islami dalam pembelajaran IPA sebagai sumber belajar yang akan dikembangkan. Metode dalam penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development) model Borg and Gall yang telahdimodifiksi yang dikembangkan melalui; 1) potensi dan masalah; 2) pengumpulan data; 3) desainproduk; 4) validasidesain; 5) revisiproduk; 6) ujicobaproduk; 7) revisiproduk. Langkah yang diambil hanya sampai dengan tujuh langkah karena keterbatasan. Data penelitian ini dikumpulkan dengan menggunakan lembar validasi, angket dan respon peserta didik. Hasil penelitian ini adalah; 1) pengembangan permainan ular tangga islami dalam pembelajaran IPA sangat layak digunakan dalam pembelajaran berdasarkan hasil validasi para ahli, yaitu ahli materi 93,5%, ahli media 80,5%, dan ahli agama 100%; 2) pada respon peserta didik yang dilakukan di tiga sekolah mendapatkan persentase kelayakan rata-rata sebesar 93% dengan kategori sangat layak.